A Conceptual Analysis of the Relationship Between Knowledge Management Capabilities and Learning Orientation Among Hoteliers in Malaysia - Nor Shahrul Nizam Muhamad Nor; Ann Gloghienette O. Perez; Nusrah Samat; Muhammad Ridzuan Abdul Aziz (Information Management and Business Review, 2024)
This study focuses on a literature review examining the impact of Knowledge Management Capabilities (KMC) and Learning Orientation (LO) among hoteliers in Malaysia. The tourism industry, one of the fastest-growing sectors, was significantly affected by Covid-19. However, it is now beginning to recover, with tourists adopting different perspectives. To maintain a competitive edge, the industry, including hoteliers, must stay abreast of the latest market trends. This requires both top management and employees to be equipped with adequate and relevant knowledge. Despite this need, some hoteliers are still reluctant to adopt knowledge management practices. Additionally, some are unable to utilize knowledge as part of their learning orientation to address changing market trends and various challenges, both micro and macro, to remain competitive. This research aims to explore how learning orientation is influenced by knowledge management capabilities, based on empirical studies. The conceptual analysis from this study can pave the way for developing a framework and further research analysis.